Proceedings of the Twenty-Fifth Symposium on Biotechnology for Fuels and Chemicals Held May 4–7, 2003, in Breckenridge, CO 2004
DOI: 10.1007/978-1-59259-837-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Moisture, and Carbon Supplementation on Lipase Production by Solid-State Fermentation of Soy Cake by Penicillium simplicissimum

Abstract: The production of lipases by Penicillium simplicissimum using solid-state fermentation and soy cake as substrate was investigated. The effects of temperature, cake moisture, and carbon supplementation on lipase production were studied using a two-level experimental plan. Moisture, pH, and lipase activity were followed during fermentation. Statistical analysis of the results was performed to evaluate the effect of the studied variables on the maximum lipase activity. Incubation temperature was the variable that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…This content was homogenized and the measurement was performed by inserting the sensor in the liquid media. All experimental conditions were determined in previous works (Di Luccio et al, 2004;Kempka et al, 2008;Vargas et al, 2008).…”
Section: Solid State Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…This content was homogenized and the measurement was performed by inserting the sensor in the liquid media. All experimental conditions were determined in previous works (Di Luccio et al, 2004;Kempka et al, 2008;Vargas et al, 2008).…”
Section: Solid State Fermentationmentioning
confidence: 99%
“…The optimized experimental conditions led to a lipase activity of 826 U/g in 12 h of fermentation, using urea (4 g/L) and olive oil (40 g/L) as nitrogen and carbon sources, respectively (Rodríguez et al, 2006). On the other hand, some authors have shown that the supplementation has no positive effect on lipases production (Di Luccio et al, 2004;Kamini, Mala, & Puvanakrishnan, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…The time and temperature fermentation in this step was defined at 48 h and 27.5°C, respectively, based on the results previously obtained using Penicillium simplicissimum [12]. All the experiments were carried out in duplicate so as to choose the best supplement as a function of the observed lipase activity.…”
Section: Supplementation Effect On Lipase Activitymentioning
confidence: 99%
“…The range of the factors investigated was selected based on previous work of the group [12]. Each assay was carried out in duplicate and a center point was performed in triplicate for experimental error evaluation.…”
Section: Optimization Of Lipase Productionmentioning
confidence: 99%
“…In this study, lipase was produced from the thermophilic and organic solvent tolerant Bacillus coagulans VKL1. Table 3 shows a comparison of different co-substrates for lipase enzyme production in accordance with different literature Benjamin and Pandey, 1997Ramachandran et al, 2007Chaturvedi et al, 2010Luccio et al, 2004 .…”
Section: Evaluation Of Agricultural Co-substrate For Lipase Productionmentioning
confidence: 85%